Displacement without Asylum: Structural and Legal Gaps in the Protection of Gazans under International Law - Nasir, Maruf Adeniyi (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2025)
Research Objective: This study examines the protection of internally displaced Gazans under international law, focusing on the interaction between International Humanitarian Law, International Human Rights Law, and refugee law during the 2023 Israel–Hamas conflict. Research Methodology: Qualitative normative legal approach grounded in Human Rights Theory and Just War Theory, analyzing primary legal sources including the Geneva Conventions, the Rome Statute, and UN resolutions, with comparative cases from Syria, Ukraine, and Sudan. Results: Legal instruments provide substantial normative protections, but implementation is severely undermined by systematic violations. Both state and non-state actors frequently breach fundamental rights to life, health, shelter, and food, while international institutions face political and structural constraints limiting effectiveness. Findings and Implications: Despite extensive legal entitlements, displaced Gazans remain unprotected due to critical normative-practical discrepancies. The UN Security Council and International Court of Justice demonstrate institutional limitations, with global enforcement challenges being systemic rather than isolated. Conclusion: Without targeted legal reforms, structural institutional changes, and enhanced accountability mechanisms, displaced populations remain vulnerable despite comprehensive legal frameworks requiring fundamental transformation. Contribution: Identifies institutional failures in civilian protection and advocates for multidimensional reform, contributing to the understanding of normative-practical discrepancies in international humanitarian law. Limitations and Suggestions: Theoretical analytical methodology limits empirical validation, and the Gaza focus may restrict generalizability. Future research should incorporate field-based studies, expand comparative analysis, and examine institutional reform effectiveness longitudinally